Effectivity of Force Letter in Optimizing Tax Revenue - et. al., Apriwandi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Not all taxpayers fulfill their tax obligations as they should. In order to safeguard the tax revenue, Indonesian government had to set some tax collection schemes, one of them was the Tax Collection by Force Letter (Penagihan Pajak dengan Surat Paksa/PSPP). Hence, the effectivity of this policy should be examined, since it was not a low-cost scheme in collecting the tax debt.Using qualitative research and a case study method at Surabaya Middle Tax Service Office (KPP Madya Surabaya), this research reviewed the data obtained in the form of legal products and the State Revenue Module in a time series basis period. Combined with interview with tax collection officers at KPP Madya Surabaya and best practices in other countries, this paper analysis the data gathered to come to a conclusion that the policy has to be reconsidered for continuing implementation, since it was not as effective as other tax collection method